Tracing the veins : of copper, culture, and community from Butte to Chuquicamata - Finn, Janet L., 1956- ([NetLibrary], 1998)
This tale of two cities - Butte, Montana, and Chuquicamata, Chile - traces the relationship of capitalism and community across cultural, national, and geographic boundaries. Combining social history with ethnography, Janet Finn shows how the development of copper mining set in motion parallel processes involving distinctive constructions of community, class, and gender in the two widely separated but intimately related sites.